Virgínia Rau : uma medievalista na Pré-história - Melo, Ana Ávila de (2016)
Professor Virgínia Rau was an eminent Portuguese medieval historian, and an international renowned researcher in economic and social history, themes that she approached during her lectures at Faculdade de Letras de Lisboa (Lisbon’s Faculty of Letters) since the late forties of the 20th century until the end of her career as full professor and college’s dean. However, during the middle and late forties of the 20th century she published a few papers on Prehistory and did some field work on Early and Middle Palaeolithic. Her interest on these themes and the reasons why she maintained this interest alive until the end of the 1940 decade and then abandoned it remain unstudied until today. In this article we intend to unveil this still unknown and mysterious aspect of Professor Virgínia Rau’s brilliant career.